Families of mirnyh and Khilchevsk: to the new facts of the biography - Potapenko , Olena (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2023)
Research aim. The article attempts to establish some facts about the early life of public figures: the spouses of Zinaida Vasylivna Mirna (Khilchevska) and Ivan Ivanovich Mirny. The author refutes some false statements regarding the milestones of Zinaida Myrna's biography, in particular, about the place and date of her birth, religion; more facts about her family have been clarified.Research methodology includes general scientific methods (analysis and synthesis) and the main methods of historical research: historical-comparative and historical-genetic.The scientific novelty. For the first time, metrical records were introduced into scientific circulation, which shed light on the early life of public figure Zinaida Vasylivna Mirnaya and her family.The relevance of the article lies in the deepening of knowledge about the figures of the Ukrainian diaspora movement, the integration of biographical information found in local studies, the formation of the basis for commemorating the memory of the fighters for the independence of Ukraine in the 20th century.Conclusions. It was found out that the Khilchevski family, from which the public member of the Ukrainian Central Council Zinaida Vasylivna Khilchevska originates, is from the Chernihiv province, where her parents lived and worked. The exact date of her birth was confirmed, false statements about her religion were denied.